Persepsi Remaja Tentang Problematika Pernikahan Dalam Seris Mendua - Beta Kurnia; Vethy Octaviani; Sapta Sari (Universitas Dehasen Bengkulu, 2023)
Adolescence is a period of exploring self-potential to form a solid personality, teenagers will later experience marriage. Currently early marriage and infidelity is one of the factors causing divorce. With so many cases of divorce due to infidelity that occur based on true stories, the filmmakers made this story into a work through a media with the aim of being able to convey the moral message of the story of infidelity to the public, one of the series that was appointed, namely Series Mendua. Series Mendua tells about the problems of marriage. In this study, the researcher chose the perspective of adolescents as research subjects, so based on this background, the researcher raised the title